2015
DOI: 10.1242/jcs.167742
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 augments Wnt signaling by stimulating β-catenin–lymphoid enhancer factor-1 complex assembly independent of β-catenin nuclear import

Abstract: ABSTRACTβ-Catenin transduces the Wnt signaling pathway and its nuclear accumulation leads to gene transactivation and cancer. Rac1 GTPase is known to stimulate β-catenin-dependent transcription of Wnt target genes and we confirmed this activity. Here we tested the recent hypothesis that Rac1 augments Wnt signaling by enhancing β-catenin nuclear import; however, we found that silencing/inhibition or up-regulation of Rac1 had no influence on nuclear accumulation of β-catenin. To better define the role of Rac1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer 43, 44, 45, 46, 47. Moreover, activation of Rac1 can increase cancer cell migration, adhesion, invasion, proliferation and metastasis 40, 44, 48, 49, 50. In our previous study, we found that miR‐124 repressed osteosarcoma cell proliferation, migration and invasion by targeting Rac1 expression 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer 43, 44, 45, 46, 47. Moreover, activation of Rac1 can increase cancer cell migration, adhesion, invasion, proliferation and metastasis 40, 44, 48, 49, 50. In our previous study, we found that miR‐124 repressed osteosarcoma cell proliferation, migration and invasion by targeting Rac1 expression 34.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is a member of the Ras superfamily of Rho proteins, and it plays an essential role in many cellular processes, including mitogenesis, kinase cascade activation, transcriptional activation, DNA synthesis and cytoskeleton reorganization [37][38][39][40][41][42]. Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer [43][44][45][46][47].…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Phosphorylation of RAC1 on Thr108 by extracellular signal-related kinase (ERK) in response to epidermal growth factor (EGF) causes RAC1 to translocate to the nucleus 32 , which is proposed to sequester it away from RhoGEFs and prevent its activation during cell migration. However, RAC1 can also regulate actin polymerization 33 and transcription factors such as β-catenin 34 and nuclear factor-κB 35 in the nucleus and thus has a distinct nuclear function. In addition, enforced localization of RAC1 to the nucleus alters the balance of RAC1 and RhoA in the cytoplasm and promotes RhoA-driven invasion 33 .…”
Section: Actomyosin Contractilitymentioning
confidence: 99%
“…Wu et al have demonstrated that Rac1 activation could cause the elevated catenin level and nuclear translocation and contribute to aberrant activation of canonical Wnt signalling in cancer cells, indicating the important roles of Rac1 in β‐catenin nuclear localization and β‐catenin‐dependent transcriptional activation . Moreover, Jamieson et al have proved that Rac1 enhanced the interaction between β‐catenin and LEF‐1, further identifying the role of Rac1 in augmenting transactivation of Wnt target genes . Buongiorno et al have demonstrated that Rac1 and the Rac1‐specific activator Tiam1 were components of transcriptionally active beta‐catenin/TCF complexes at Wnt‐responsive promoters, revealing a novel functional mechanism underlying the cross‐talk between Rac1 and the canonical Wnt signalling pathway in colorectal cancer cells .…”
Section: Discussionmentioning
confidence: 99%